PROBLEM LUSTRACJI W KRAJACH EUROPY ŚRODKOWO-WSCHODNIEJ I W KRAJACH BAŁTYCKICH - Opalińska, Agnieszka (In Gremium. Studies in History, Culture and Politics, 2019)
The political transformation in Central and Eastern Europe has stabilised democracy there. Democratic institutions have been established and the rule of law protects people’s freedoms. However, the previous regimes have been dealt with in a variety of ways. The vetting laws in particular countries differ from each other and involve different legal measures. Yet, they are on common ground with regard to de-communisation and access to secret police files. This paper discusses one aspect of dealing with the past: the vetting law, as applied to persons whose past involved – in any way – the secret police. The solutions adopted in the following countries are presented: Poland, former German Democratic Republic, the Czech Republic, Hungary, Bulgaria, Romania, Slovakia, Estonia, Lithuania, and Latvia. Because of the complexity of the vetting law with regard to its legal, political, and social aspects, this paper tries to define and classify it. The theoretical discussion is exemplified by the solutions adopted in particular countries. The conclusions offer a comparison of the vetting laws in the Central and Eastern European countries and show that the vetting law still remains an unresolved issue, thus producing negative socio-political fallout.